(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The most popular kind of energy is electrical energy. Large power plants often create it, and the national grid then distributes it to other areas. It is obvious that India’s supply of electrical energy is inadequate because of some challenging geographic features like terrain, mountains, and flood plains. Additionally, power is typically of poor quality, and outages happen frequently. Maintaining the household and light industrial load in this situation is challenging. In this study, wind energy is integrated with solar photovoltaic (PV) technology. Due to the intermittent nature of both sources, a battery bank with sufficient capacity has been installed to ensure supply continuity. Simulated in standalone mode is the system. The plan looks at various pairings, assesses cost effectiveness, and studies pollutant emission reduction. The plan attempts to recommend the ideal size of the solar PV-wind integration and the system’s BoS, which will be able to deliver appropriate power quality with improved reliability and a minimal levied cost of energy.